Dorothy Dean's homemakers service - Dean, Dorothy, pseud (The Spokesman-Review, 1970)
Dorothy Dean was a pseudonym for The Spokesman-Review's Home Economics Department, which started 1935 and closed in 1983. The Dorothy Dean Homemakers service distributed leaflets (three each month for 11 months, with an index to the recipes on the 12th month) which subscribers collected in a green binder.